1979
DOI: 10.1042/bj1830683
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of zinc-binding protein from the liver of the partially hepatectomized rat

Abstract: Zn-binding protein in liver of the partially hepatectomized rat was purified by column chromatography on Sephadex G-75 and DEAE-cellulose. Homogeneity was judged by polyacrylamide-disc-gel electrophoresis. The molecular weight determined by gel-permeation chromatography in 6 M-guanidine hydrochloride was 6700. This value is in good agreement with the molecular weight calculated from the amino acid composition, which was 6073. Zn-binding protein was composed of 61 amino acid residues, and the distinctive featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…This is indicated by dramatic differences in gene expression (21,52,53). For example, after partial hepatectomy MT was observed to accumulate in regenerating liver cells, the classic in vivo prototype of Go cells that are reentering S phase and mitosis (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…This is indicated by dramatic differences in gene expression (21,52,53). For example, after partial hepatectomy MT was observed to accumulate in regenerating liver cells, the classic in vivo prototype of Go cells that are reentering S phase and mitosis (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…This result shows active proliferation of glial cells in the newborn mouse, and so in the fetal brain glial cells may be actively proliferating and re newed. Ohtake and Koga [10] believed that MT was important in the regulation of DNA synthesis through the synthesis or activity of enzymes required for nucleic acid. Nishimura et al [11] also demonstrated the possible involvement of MT in cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…MT was found in the nuclei, cytoplasmic process and vascular feet of both protoplasmic and fibrous astrocytes. MT may be involved in detoxification of heavy metals and may also play a role in the storage, transport, absorption, excretion and homeostasis of heavy metals in the tissues (6 (18) considered that MT was important in the regulation of DNA synthesis through the synthesis or activity of enzymes required for nucleic acid. Nishimura et al (17) have also demonstrated a possible involvement of MT in cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%